(untitled) (The Research of Medical Science Review, 2025)
The current study aims to investigate the dry fig and apricot jam as a dietary intervention to reduce hypertension. During the present research treatments were prepared using dry figs and apricots i.e T0a (100% dry figs), T0b (100% dry apricot), T1 (75% dry apricot and 25% dry figs), T2 (50% dry apricot and 50% dry figs) and T3 (75% dry figs and 25% dry apricots) Physicochemical parameters such as total acidity, total soluble solids (TSS) and sugars were analyzed on the 0, 15th and 30th day of month. Total Phenolic Content (TPC) and DPPH radical scavenging activity were used to evaluate antioxidant qualities. It was observed that T1 has the highest TPC (510.50 mg GAE/100) and T3 has highest DPPH (43.15%). Both of these parameters decreased with time. The Sensory parameters i.e color, taste, texture and overall acceptability was analyzed and indicated that T1 (75% dry apricot and 25% dry figs) was preferred by all panelists. This research suggests that the formulated jams could potentially offer health benefits related to hypertension and underscores the importance of antioxidant-rich dietary interventions.